Utilization of the Rumah Budaya Museum as a Source for Learning History in Banda Naira - Winto Winto; Abrar Abrar; Umasih Umasih (STAI Miftahul Ula Nganjuk, 2023)
this study aims to determine the use of the Rumah Budaya Museum in Banda Naira as a source of learning about history. The research method used is qualitative, with a case study approach. The data collection techniques used are observation, interviews, and documentation. The research subjects included history teachers, students, and Rumah Budaya Museum managers. The results of the study show that: (1) the role of the history teacher in utilizing the Rumah Budaya Museum as a source of history learning is to plan, implement, and evaluate history lessons by referring to competency standards and essential competencies that are appropriate to regional history material; (2) students' learning motivation when visiting the Rumah Budaya Museum is high because they can directly see, touch, and study historical objects in the museum; (3) the obstacles faced by history teachers and students in utilizing the Rumah Budaya Museum as a source of history learning are time, cost, and licensing limitations. This study provides suggestions so related parties can work together to overcome these obstacles and develop a history-learning design that utilizes the Rumah Budaya Museum as a source of history learning.